2001
DOI: 10.1074/jbc.m102860200
|View full text |Cite
|
Sign up to set email alerts
|

The Kissing Hairpin Sequence Promotes Recombination within the HIV-I 5′ Leader Region

Abstract: The role of RNA-RNA template interactions in facilitating recombination during reverse transcription of minus strand DNA has been examined. The tested hypothesis is that template switching by reverse transcriptase is promoted at sites where homologous regions of two RNAs are brought in close proximity via stable intertemplate interactions. Frequency and distribution of template switching between homologous donor and acceptor RNAs were examined within the human immunodeficiency virus type I (HIV-I) 5-untranslat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
93
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(96 citation statements)
references
References 75 publications
2
93
1
Order By: Relevance
“…It was first suggested that the hairpins formed by these regions could favor template switching by increasing the spatial proximity between the donor and the acceptor RNAs through an intermolecular interac- tion occurring within the hairpin region (13,16,17). Our results do not support such an interpretation because here the hairpin structure is not required on the donor RNA and, therefore, cannot act by mediating an interaction with the acceptor RNA.…”
Section: Fig 4 Primer Extension Assayscontrasting
confidence: 56%
See 2 more Smart Citations
“…It was first suggested that the hairpins formed by these regions could favor template switching by increasing the spatial proximity between the donor and the acceptor RNAs through an intermolecular interac- tion occurring within the hairpin region (13,16,17). Our results do not support such an interpretation because here the hairpin structure is not required on the donor RNA and, therefore, cannot act by mediating an interaction with the acceptor RNA.…”
Section: Fig 4 Primer Extension Assayscontrasting
confidence: 56%
“…In parallel, studies carried out on RNA templates containing hairpin regions have suggested that such structures could favor template switching by RTs (13,16,17). In these cases it was proposed that the hairpin structures enhance the probability of strand transfer by mediating an interaction between donor and acceptor RNA that increases their spatial proximity (13,16,17).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Recent studies in our laboratory have shown evidence for an acceptor invasion-initiated mechanism for internal transfer events that lead to recombination (56,78). Transfers occur through a two-step "dock and lock" mechanism, where the acceptor interacts (docks) with the donor-cDNA complex at regions where RNase H cleavage is enhanced (76,78).…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro works have suggested an implication of hairpin structures in promoting copy choice by bringing donor and acceptor RNAs into close proximity (33,34) or by favoring pausing of reverse transcription at the base of the hairpin followed by strand transfer within the hairpin region (20). Based on an in vitro study of the same C2 sequence studied here, we previously proposed that strand transfer would begin by the docking of the nascent DNA onto the acceptor RNA in the loop of the hairpin and would then proceed through a process of strand exchange similar to branch migration occurring during DNA-DNA recombination (10).…”
Section: Discussionmentioning
confidence: 99%